Emotional Intelligence and Academic Achievement of Adolescents: Understanding the Relationship Between Emotional Intelligence and Academic Achievement in Adolescents (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Children's attitudes toward academic achievement might vary widely. Some may thrive onstructure, while others may want to experiment with different approaches. If one child is organized andmethodical, the other youngster may be unorganized or haphazard. People's unique ways of thinking andlearning contribute to this. Mismatches in teaching methods are prevalent in academic institutions.Because learning disparities are not linked to students' abilities to comprehend and think, the teacher'steaching and thinking styles and the students' learning and thinking styles diverge. Teachers andstudents of all ages will benefit from this knowledge since it will help them better comprehend and applythe results to their classrooms. Understanding how different learning and cognitive styles, as well asemotional intelligence, are related to academic achievement may be beneficial for students.